Wacana Multimodal Pada Billboard Bacapres 2024 - Rudi Haryatno, Yulius (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
One of the visual displays that has attracted the attention of the public and Indonesian political observers aheadof the 2024 presidential election (Pilpres) is the billboard for presidential candidates (Bacapres) PrabowoSubianto (PS) and Ganjar Pranowo (GP), each of whom is side by side with President Jokowi Dodo. OnlyBacapres Anies Baswedan (AB) did not display the figure of President Joko Widodo on his billboards or politicaladvertising space. Because Bacapres AB operates under the